The Influence of Harvested Land Area, Labor, and Working Capital on Rice Production in Penebel District, Tabanan Regency - Ni Gusti Ayu Dwi Widyari; Sudarsana Arka (International Journal of Management Research and Economics, 2025)
The agricultural sector, particularly the food crop subsector namely rice plays a crucial role in the regional economy, especially in ensuring the supply of staple food. Tabanan Regency, located in Bali Province, is widely recognized as the "rice barn" of the region. Despite its substantial rice production, the region faces a significant threat from land-use conversion, which endangers the area of rice fields in Tabanan Regency. Penebel District, as the largest rice-producing area in the regency, is particularly vulnerable to this phenomenon. The objectives of this study are: (1) to analyze the simultaneous effect of harvested land area, labor, and working capital on rice production in Penebel District, Tabanan Regency; and (2) to analyze the partial effect of harvested land area, labor, and working capital on rice production in the same region. This study uses primary data collected through interviews using questionnaires with 100 rice farmers selected using proportionate stratified random sampling. The analytical method employed is multiple linear regression analysis using the EViews software. The results indicate that: (1) harvested land area, labor, and working capital simultaneously have a significant effect on rice production in Penebel District, Tabanan Regency; and (2) harvested land area and working capital have a positive and significant partial effect on rice production, while labor does not have a significant effect.